1993
DOI: 10.1002/bem.2250140306
|View full text |Cite
|
Sign up to set email alerts
|

Early pregnancy loss and exposure to 50‐Hz magnetic fields

Abstract: The possibility of an association of early pregnancy loss (EPL) with residential exposure to ELF magnetic fields was investigated in a case-control study. Eighty-nine cases and 102 controls were obtained from the data of an earlier study aimed at investigating the occurrence of EPL in a group of women attempting to get pregnant. Magnetic-field exposure was characterized by measurements in residences. Strong magnetic fields were measured more often in case than in control residences. In an analysis based on fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
1
2

Year Published

1996
1996
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 20 publications
2
50
1
2
Order By: Relevance
“…In epidemiologic studies indications of possible increased risks have been found at field strengths of 0.4-1.5 J.lT (59), 1 J.lT (60), or above 0.5 A im (0.6 J.lT) (61). These values agree fairly well with the experimental data suggesting a threshold of 1 A im for the effects on chick embryos (20).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In epidemiologic studies indications of possible increased risks have been found at field strengths of 0.4-1.5 J.lT (59), 1 J.lT (60), or above 0.5 A im (0.6 J.lT) (61). These values agree fairly well with the experimental data suggesting a threshold of 1 A im for the effects on chick embryos (20).…”
Section: Discussionsupporting
confidence: 80%
“…A case-referent study was conducted in Finland to investigate the possible association of early pregnancy field exposure (61). Eighty-nine cases and 102 referents were obtained from the data of an earlier study aimed at investigating the incidence of early pregnancy loss in a group of women attempting to get pregnant.…”
Section: Epidemiologic Studiesmentioning
confidence: 99%
“…Juutilainen et al [9] showed that women with early pregnancy losses (subclinical) were more likely to live in residences with strong 50-Hz magnetic fields than were woman with normal pregnancies.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to spontaneous abortion, high-intensity magnetic fields measured at the front doors of homes of volunteers' homes in a "work and fertility" cohort study in Finland, were associated with a marginally significant, 5-fold increased risk (based on fewer than 10 cases and adjusted only for smoking status) (195). Two later studies, Savitz and Anath (196) and Belanger et al (197), found no increase in risk of spontaneous abortion however.…”
Section: Reproductive Effectsmentioning
confidence: 97%